2018
DOI: 10.4049/jimmunol.1800330
|View full text |Cite
|
Sign up to set email alerts
|

Seropositivity and Antibody Profiling of Patients Are Dramatically Impacted by the Features of Peptides Used as Immunosorbents: A Lesson from Anti–Citrullinated Protein/Peptide Antibody

Abstract: Quantification of Abs toward a single epitope is critical to understanding immunobiological processes. In autoimmunity, the prognostic value of the serological profiles of patients draws much attention, but the detection of Abs toward a single epitope is not well controlled. Particularly, the rheumatoid arthritis (RA)–specific anti–citrullinated protein/peptide Abs (ACPA) are specific to a two-atom change on arginyl residues and are considered a heterogeneous family of Abs. As a model, we studied ACPA to decip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 56 publications
2
5
0
Order By: Relevance
“…Indeed, we showed that minor changes in peptide structure dramatically impacted ELISA results. 13 This is confirmed in the present work showing that the Nt-biotinylation of b60-74Cit and the cyclisation of CEP-1 considerably enhance ACPA capture. This underlines the difficulty to clearly define ACPA fine specificities and thus highlights the relativity of final conclusions concerning ACPA profiles.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Indeed, we showed that minor changes in peptide structure dramatically impacted ELISA results. 13 This is confirmed in the present work showing that the Nt-biotinylation of b60-74Cit and the cyclisation of CEP-1 considerably enhance ACPA capture. This underlines the difficulty to clearly define ACPA fine specificities and thus highlights the relativity of final conclusions concerning ACPA profiles.…”
Section: Discussionsupporting
confidence: 87%
“…Antibodies towards the biotinylated form of the b60-74 peptide (b60-74CitBiotNt), AhFibA and anti-CCP2 antibodies (Immunoscan RA; Euro Diagnostica, Arnhem, The Netherlands) were tested as previously described. 12,13…”
Section: Peptide and Antibody Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…However in the present study, the peptides were used biotinylated and linked to Avidin versus immunoadsorbed on solid phase in the pilot study. Such an increased reactivity when using biotinylated peptides, depending on a different presentation of the peptides, was clearly demonstrated with the peptide β60-74cit in a recently published study ( 33 ).…”
Section: Discussionmentioning
confidence: 63%